Catching-up in Europe: The Experiences of Portugal, Spain and Greece in the Nineties - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2003)
Economic performance in developed economies diverged in the nineties, with some countries enjoying high growth in output and accelerating growth in productivity. Ireland excelled in many respects and some Nordic European countries recovered from a serious crisis and successfully regained strong growth rates. In general the nineties were a disappointing decade for Europe as compared to the eighties as well as to the USA. This article investigates the performances of the three southern peripheral economies, Spain, Portugal and Greece, over the long run but specifically in the nineties. It then relates performance to indicators of cost, regulation and investment into future growth. The convergence process is different in speed, scope and time pattern in the three countries. Long term growth is about one percentage point higher in all three countries than in the EU. Convergence had been strong in the sixties, disappointing and very different for the three countries in the seventies and eighties. In the difficult period of the nineties and including the crisis of 2000/2003 the three southern peripheral countries successfully resumed a catching-up strategy. The growth differential in the nineties is however much smaller than in Ireland, it is less for productivity than for real growth and per capita income.
Keywords: 330; convergence; catching up; periphery; economic performance; growth determinants; Wirtschaftswachstum; Wirtschaftliche Konvergenz; Schätzung; Portugal; Spanien; Griechenland